The greener, the richer, the happier?——Spatial distribution and coupling analysis of urban green space and residents’ emotion based on social media data - Zexun Li; Lihui Hu; Alin Lin; Jiarui Chen; Yue Xu (Ecological Indicators)
The emotional well-being and welfare of urban residents are intricately linked to their surrounding living environments. Urban development in China has progressively placed greater emphasis on the human settlement environment. And has introduced policies such as urban regeneration and low-carbon community construction, which are aimed at upgrading urban quality and improving the well-being of the people. An increasing amount of attention is being drawn by users, managers, and designers towards the design of urban green spaces that take into account the emotional considerations of the residents. The explosive growth of social media has presented novel opportunities to explore the correlation between residents’ emotions and urban green spaces. Research on the traditional correlation between urban green spaces and residents’ emotions has been constrained by limited individual sample sizes, resulting in a generally narrow research scope and a relatively homogeneous set of factors considered. This study, taking the urban area of Hangzhou as a case study, investigates the relationship between NDVI, residential prices, and emotional value at the city scale. Through the application of the Coupling Coordination Degree Model and the Mediation Effect Model, the study specifically focuses on the efficiency and fairness of urban green space distribution. The findings reveal that the emotional value within the study area spans from −8 to 19, with positive emotions comprising 49.73% of the total. However, these emotions exhibit a scattered spatial distribution. The mediation effect analysis reveals that an increase in NDVI by 1% leads to a 0.178% growth in emotional value, while a rise by 1% in residential prices decreases in emotional value by 0.109%. By leveraging social media data as evidence has provided a fresh research perspective on the developmental trajectory of green spaces. It has also discovered that enhancing the quality and functionality of green spaces can boost urban well-being, offering valuable guidance to planners in the context of park city.